2011
DOI: 10.1002/mus.22239
|View full text |Cite
|
Sign up to set email alerts
|

Skin biopsy–proven flecainide‐induced neuropathy

Abstract: Flecainide acetate is a classic Ic antiarrhythmic agent used to treat a variety of cardiac arrhythmias. Non-cardiac side effects usually affect the central nervous system. Few case reports of possible flecainide-induced peripheral neuropathy have been reported. We report this unique case in that flecainide-induced sensory neuropathy was confirmed with skin biopsy, and subsequent improvement of neuropathy was documented with assessment of intraepidermal nerve fiber density in a repeat nerve biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Indeed, it has been shown in cultured dorsal root ganglia expressing small fiber neuropathy-associated G856D mutant Nav1.7 channels that degeneration of neurites [ 35 ] is promoted by a decrease in ATP levels and increase in intracellular calcium levels [Ca 2+ ] i , which would be expected as a consequence of mitochondrial damage and depletion. Selective loss of small-diameter myelinated axons occurs in CNS in multiple sclerosis [ 36 ], and it is especially prominent in small fiber neuropathies (SFN), which are often characterized by pain and autonomic symptoms, including diabetic neuropathy [ 37 39 ], chemotherapy-associated neuropathy [ 40 ], HIV [ 41 ], systemic lupus erythematosus [ 42 ], paraneoplastic syndrome [ 43 ], sarcoidosis [ 44 ], drug toxicity [ 45 47 ], hereditary neuropathies [ 48 ], familial amyloidosis [ 49 ], and inflammatory peripheral neuropathy and Guillain-Barré syndrome (GBS) [ 42 ]. The pervasive vulnerability of small-diameter axons is striking, and the mechanisms described in this paper may contribute to their selective vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown in cultured dorsal root ganglia expressing small fiber neuropathy-associated G856D mutant Nav1.7 channels that degeneration of neurites [ 35 ] is promoted by a decrease in ATP levels and increase in intracellular calcium levels [Ca 2+ ] i , which would be expected as a consequence of mitochondrial damage and depletion. Selective loss of small-diameter myelinated axons occurs in CNS in multiple sclerosis [ 36 ], and it is especially prominent in small fiber neuropathies (SFN), which are often characterized by pain and autonomic symptoms, including diabetic neuropathy [ 37 39 ], chemotherapy-associated neuropathy [ 40 ], HIV [ 41 ], systemic lupus erythematosus [ 42 ], paraneoplastic syndrome [ 43 ], sarcoidosis [ 44 ], drug toxicity [ 45 47 ], hereditary neuropathies [ 48 ], familial amyloidosis [ 49 ], and inflammatory peripheral neuropathy and Guillain-Barré syndrome (GBS) [ 42 ]. The pervasive vulnerability of small-diameter axons is striking, and the mechanisms described in this paper may contribute to their selective vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…In a collaborative study, 3% of cases receiving antiarrhythmic drugs, including amiodarone, showed clinical polyneuropathy, while 25% presented electrophysiological findings in keeping with a diagnosis of polyneuropathy [7]. Burakgazi et al [14] reported a unique case of neuropathy affecting small nerve fibers induced by flecainide, another commonly used antiarrhythmic agent; the neuropathy was confirmed by skin biopsy with improvement associated with increased of intraepidermal fiber density 16 months after flecainide withdrawal. Three patients of Fraser et al [1] during long-term high-dose therapy developed predominantly sensory neuropathy; high concentrations of amiodarone and its N-desethyl metabolite were found in lysosomes especially in tissues rich of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol abuse (Koike and Sobue, 2006), statins (Lo et al, 2003), metronidazole (Tan et al, 2011), flecainide (Burakgazi et al, 2012), nitrofurantoin (Tan et al, 2012), linezolid (Chao et al, 2008), antiretroviral drugs (Ferrari and Levine, 2010), chemotherapy agents (Geber et al, 2013) Immune-mediated Sarcoidosis (Heij et al, 2012), amyloidosis (Adams et al, 2012), Sj€ ogren syndrome (Chai et al, 2005), systemic lupus erythematosus (Gøransson et al, 2006), inflammatory bowel disease (Gondim et al, 2005), celiac disease , paraneoplastic syndromes (Gorson et al, 2008) Neurodegenerative Parkinson's disease (Rossi et al, 2007), amyotrophic lateral sclerosis (Weis et al, 2011) Idiopathic Underlying cause not known, including burning mouth syndrome (Lauria et al, 2005c) with no obvious medical or dental cause. The prevalence ranges from 3.7% to 18%, with a higher prevalence in postmenopausal women (Bergdahl and Bergdahl, 1999;Grushka et al, 2002;Jääskeläinen, 2012).…”
Section: Drug and Toxic Causesmentioning
confidence: 99%